2018
DOI: 10.5811/westjem.2017.10.36027
|View full text |Cite
|
Sign up to set email alerts
|

Does the Podcast Video Playback Speed Affect Comprehension for Novel Curriculum Delivery? A Randomized Trial

Abstract: IntroductionMedical education is a rapidly evolving field that has been using new technology to improve how medical students learn. One of the recent implementations in medical education is the recording of lectures for the purpose of playback at various speeds. Though previous studies done via surveys have shown a subjective increase in the rate of knowledge acquisition when learning from sped-up lectures, no quantitative studies have measured information retention. The purpose of this study was to compare me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 2 publications
1
18
0
Order By: Relevance
“…However, for a student who has missed the live session, there is a need to review the full lecture. Song et al (2018) provide evidence that if a video is watched at 1.5x normal speed then test performance is negatively impacted, and so there is a strong recommendation that students watch the recording at normal speed the first time it is viewed. This also ensures that time-on-task (Carroll, 1989) is comparable between those who attended and those who watched the recording Although there is convincing evidence that attending live lectures leads to better outcomes than only watching a recording (e.g., Bos et al, 2016) there is still no definitive answer as to why this may be the case.…”
Section: If It Is Notmentioning
confidence: 99%
“…However, for a student who has missed the live session, there is a need to review the full lecture. Song et al (2018) provide evidence that if a video is watched at 1.5x normal speed then test performance is negatively impacted, and so there is a strong recommendation that students watch the recording at normal speed the first time it is viewed. This also ensures that time-on-task (Carroll, 1989) is comparable between those who attended and those who watched the recording Although there is convincing evidence that attending live lectures leads to better outcomes than only watching a recording (e.g., Bos et al, 2016) there is still no definitive answer as to why this may be the case.…”
Section: If It Is Notmentioning
confidence: 99%
“…Although Perez (2017) and Song et al (2018) found significant negative influence of 1.5x playback speed on cognitive learning outcomes, other studies including Pastore (2010Pastore ( , 2012, found non-significant influence of playback speed at 1.5x. Furthermore, found non-significant effect at 1.4x and demonstrated that moderately accelerated playback speed at 1.25x had no significant difference in cognitive learning outcomes when compared to normal playback speed.…”
Section: Findings From Researchmentioning
confidence: 80%
“…Although Perez (2017) and Song et al. (2018) found significant negative influence of 1.5x playback speed on cognitive learning outcomes, other studies including Pastore (2010, 2012), Ritzhaupt and Barron (2008), and Ritzhaupt et al.…”
Section: Discussionmentioning
confidence: 97%
“…Previous work on the effect of video speed on learning has yielded mixed results. For example, there is some evidence that increasing the speed of videos leads to preserved or enhanced comprehension (Lang et al, 2020; Nagahama & Morita, 2017; Wilson et al, 2018) while other work suggests that increased speed impairs comprehension (Foulke & Sticht, 1969; Song et al, 2018; Vemuri et al, 2004). To further examine the impact of lecture video speed on comprehension, in Experiment 1, we tested learners' immediate and delayed (1 week) comprehension after watching videos at either 1x, 1.5x, 2x, or 2.5x speed.…”
Section: Discussionmentioning
confidence: 99%
“…Watching asynchronous lectures at a higher speed may be a useful and efficient study strategy if it results in similar or better comprehension than when watching lectures at a normal speed; however, there has been some disagreement regarding the effect of video speed on comprehension. For example, some work has found that increasing the speed of videos can preserve or even enhance comprehension (Lang et al, 2020; Nagahama & Morita, 2017; Wilson et al, 2018) while others suggest that increased speed impairs comprehension (Foulke & Sticht, 1969; Song et al, 2018; Vemuri et al, 2004). These disagreements may be the product of using limited stimuli, measuring comprehension immediately after watching the video (rather than a delayed test), allowing for note‐taking and participant control of the videos (i.e., pausing, rewinding), using very short video clips (i.e., 20 s), and small sample sizes.…”
mentioning
confidence: 99%